The Effects of Macroeconomic Fundamentals on the Stock Prices Movement in Selected Countries - Peck Ching, Sia (2023)
For centuries, the stock market has been the backbone of the economy serving as a crucial platform for buying and selling securities. This study contributes to investigate the symmetric and asymmetric effects of macroeconomic fundamentals on stock prices of the selected countries: Indonesia, Malaysia, and Singapore. Generally, these three countries have different stages of development where Indonesia and Malaysia are both emerging countries while Singapore is a developed country. These three ASEAN countries have various monetary policies in addition to their disparate economic condition. Previous research has thoroughly investigated the relationship between stock prices and macroeconomic issues, but it was believed that the relationship is symmetrical. There is a scarcity of empirical information on the asymmetric effect of macroeconomic fundamentals on stock prices. This study using two different approaches: autoregressive distributed lag (ARDL) approach and nonlinear autoregressive distributed lag (NARDL) to overcome the limitation of previous studies. The study used time series data based on quarterly observations from 1999 to 2021. Given the results, inflation, interest rate, and exchange rate show nonlinear effect on stock prices in Indonesia. In Malaysia, the results show nonlinear effect of interest rate and exchange rate on stock prices. However, most of the models are insignificant for Singapore. Therefore, policymakers should optimize the asymmetric effect of inflation, interest rate, and exchange rate according to the nature of each country.